2020
DOI: 10.1159/000511883
|View full text |Cite
|
Sign up to set email alerts
|

Early HER2-Positive Breast Cancer: Current Treatment and Novel Approaches

Abstract: <b><i>Background:</i></b> Trastuzumab significantly improves outcomes in early HER2-positive breast cancer, irrespectively of any prognostic or predictive factors. Unfortunately, about a quarter of patients receiving neoadjuvant trastuzumab experience disease recurrence, revealing the unquestionable need for further improvement of treatment outcomes. <b><i>Summary:</i></b> Adding HER2 blockade to adjuvant trastuzumab with pertuzumab and neratinib improves invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
(53 reference statements)
0
10
0
4
Order By: Relevance
“…The latter was a conditional approval which had to be confirmed in the positive adjuvant Aphinity trial [16]. All these trials led to wide implementation of the combination in HER2-positive patients [17]. Thus, it can be expected that trastuzumab biosimilars will be widely implemented in this combination to lower the total costs of the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter was a conditional approval which had to be confirmed in the positive adjuvant Aphinity trial [16]. All these trials led to wide implementation of the combination in HER2-positive patients [17]. Thus, it can be expected that trastuzumab biosimilars will be widely implemented in this combination to lower the total costs of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the phase III CLEOPATRA trial, the combination of pertuzumab with trastuzumab and docetaxel improved progression-free survival and overall survival when compared to trastuzumab and docetaxel alone [12,13]. The efficacy and safety of both HER2-directed agents in combination with chemotherapy was also confirmed in the neoadjuvant setting, demonstrating low rates of CD when pertuzumab and trastuzumab were given in combination with anthracycline-free chemotherapy, but also with anthracycline-containing regimens [14][15][16][17]. Cardiac safety was confirmed in a 5-year follow-up [18].…”
Section: Introductionmentioning
confidence: 94%
“…Trastuzumab is a turning point in treating breast cancer patients with HER2 overexpression/amplification [ 8 ]. Its implementation leads to improved DMFS [ 20 ], DFS [ 8 , 20 ], OS [ 8 ] and even locoregional relapse-free survival [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trastuzumab is a turning point in treating breast cancer patients with HER2 overexpression/amplification [ 8 ]. Its implementation leads to improved DMFS [ 20 ], DFS [ 8 , 20 ], OS [ 8 ] and even locoregional relapse-free survival [ 20 ]. This retrospective study demonstrated that trastuzumab is the leading systemic therapy associated with improved outcomes, even compared to an adequate multimodal systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation